Implementation of folk story to improve accounting students' mastery of past tense sentences - Prihamdani, Depi; Hidayat, Soleh; Jamaludin, Ujang; Leksono, Suroso Mukti (Nashir Al-Kutub Indonesia, 2023)
The aims of this study were to find out: 1) the extent to which students' competence in past tense sentences, and 2) the significant effect of using folklore on students' competence in past tense sentences in semester 2 students majoring in accounting. program of the Faculty of Economics and Business, Buana Perjuangan University, Karawang. This research method is a quantitative method. Researchers collected data by using a written test. Samples were taken using a random sampling technique of 35 students. The data were then analyzed using descriptive and inferential analysis, namely the t-test formula by Arikunto. The results of this study were that the average score of students' competence in past tense sentences before using folklore was 51.5 which was categorized as